2020
DOI: 10.1039/c9qi01147a
|View full text |Cite
|
Sign up to set email alerts
|

A Pd3L6 supramolecular cage incorporating photoactive [2.2]paracyclophane units

Abstract: In this work we report two photoactive [2.2]paracyclophane (pCp) ligands and a luminescent Pd3L6 cage incorporating these ligands, which exhibits blue emission both in solution and in the powder state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
1
15
0
2
Order By: Relevance
“…for C 26 H 23 N 2 363.18; Found 363.07. Compound impure but major component matches data in literature [8j] . 4‐(Pyridin‐3‐ylthio)‐12‐(pyridin‐3‐yl)[2.2]paracyclophane 28 1 H NMR (CDCl 3 , 500 MHz): δ 8.83 (1H, d, J =1.6 Hz), 8.62 (1H, dd, J =4.8, 1.5 Hz), 8.47 (1H, d, J =1.8 Hz), 8.37 (1H, dd, J =4.7, 1.4 Hz), 8.00 (1H, ddd, J =7.9, 4.2, 2.1 Hz), 7.45 (1H, dd, J =7.2, 4.2 Hz), 7.42 (1H, ddd, J =8.0, 3.9, 1.6 Hz), 7.13 (1H, ddd, J =7.9, 4.7, 0.4 Hz), 6.95 (1H, d, J =1.7 Hz), 6.74–6.68 (3H, m), 6.62 (2H, dd, J =7.3, 1.7 Hz), 3.51–3.43 (2H, m), 3.29–3.20 (2H, m), 2.93–2.82 (3H, m), 2.46–2.36 (1H, m); ESI‐TOF m/z : [M+H] + calcd.…”
Section: Methodssupporting
confidence: 84%
See 3 more Smart Citations
“…for C 26 H 23 N 2 363.18; Found 363.07. Compound impure but major component matches data in literature [8j] . 4‐(Pyridin‐3‐ylthio)‐12‐(pyridin‐3‐yl)[2.2]paracyclophane 28 1 H NMR (CDCl 3 , 500 MHz): δ 8.83 (1H, d, J =1.6 Hz), 8.62 (1H, dd, J =4.8, 1.5 Hz), 8.47 (1H, d, J =1.8 Hz), 8.37 (1H, dd, J =4.7, 1.4 Hz), 8.00 (1H, ddd, J =7.9, 4.2, 2.1 Hz), 7.45 (1H, dd, J =7.2, 4.2 Hz), 7.42 (1H, ddd, J =8.0, 3.9, 1.6 Hz), 7.13 (1H, ddd, J =7.9, 4.7, 0.4 Hz), 6.95 (1H, d, J =1.7 Hz), 6.74–6.68 (3H, m), 6.62 (2H, dd, J =7.3, 1.7 Hz), 3.51–3.43 (2H, m), 3.29–3.20 (2H, m), 2.93–2.82 (3H, m), 2.46–2.36 (1H, m); ESI‐TOF m/z : [M+H] + calcd.…”
Section: Methodssupporting
confidence: 84%
“…The coupling of both sodium 3‐pyridine sulfinate 8 and the 4‐pyridine sulfinate 9 were even less successful. The poor coupling was disappointing as both of these bispyridines can be prepared in good yield using standard Suzuki‐Miyaura couplings, [8j] 27 in 70% and 30 in 75% compared to our 13% and 0% respectively (compound 27 can be identified in the 1 H NMR but is contaminated with bipyridine). At present, it is unclear why the sulfinate chemistry is struggling with pseudo ‐ ortho ‐dibromo[2.2]paracyclophane more than the other bromo compounds.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The two benzene rings of the [2.2]paracyclophane (pCp) are disposed cofacially (Bahrin et al, 2017, 2), which give rise to through-space (π-π trans-annular) and through-bond [σ(bridge)-π(annular)] electronic interactions, affecting the chemical, optical, and electronic properties of the molecule (Kahnt et al, 2007;Elacqua and MacGillivray, 2010). It has been shown that positioning organic functional groups on the pCp core ring shifts its luminescence properties (Braun et al, 2017;Anhäuser et al, 2019;Rota Martir et al, 2019). Exploiting the electronic coupling present between the two benzene decks of the pCP, the first examples of pCp compounds emitting via a thermally activated delayed fluorescence mechanism were recently reported by Spuling, Sharma and coworkers (Spuling et al, 2018).…”
Section: Introductionmentioning
confidence: 99%